Differing radiation exposure in scrub technicians and rotating staff in cardiac catheterization laboratory: occupation matters. (4th February 2022) - Javed, M; Rahman, N; Adnan, G; Nizar, Z; Shah, I
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Radiation exposure of cardiac catheterization lab personnel is an evolving area of concern, due to long term, repetitive exposure causing deterministic and stochastic effects(1, 2). Current radiation protection measures are based on increasing distance, shielding from fluoroscopy source and depend on primary operator behavior(3) Effective dose(ED) in micro Sieverts( μSv) as a measure of individual absorbed radiation dose provides feedback as to occupational exposure and risks. Dosimeter badges worn over equipment measure ED correlating with radiation exposure of areas unprotected by standard lead apron such as head, neck, lens and upper limbs. (4) Most studies focus on primary operator exposure (5, 6, 7), overlooking non physician staff comprising scrub technicians working as assistants to primary operator physicians, and rotating staff involved in peri-procedural care of patients. Purpose: This study aimed to find out ED acquired by scrub technicians(ED.S) and rotating staff(ED.R) in interventional cardiology and invasive electrophysiology procedures, utilizing external dosimeters worn over lead aprons. Methods: We prospectively collected radiation data over forty six invasive Cardiology procedures from 15th March 2021 to 1st June 2021 comprising fourteen diagnostic coronary and graft angiograms, seventeen combined diagnostic and interventional cardiology procedures, nine sole percutaneous coronary interventions and six electrophysiology procedures. Nine staff members: two female and seven male members participated as scrub technicians and rotating staff, provided with external dosimeter badges. ED was obtained by logging in dosimeter badges into pre calibrated monitors. Results: Significantly high mean ED was acquired by rotating staff as compared to scrub technicians, mean ED.R:21.04 μSv( SD: +/-39.64) and mean ED.S: 7.54 μSv( SD:+/- 17.23), this three fold difference in radiation exposure was statistically significant with a p-value of 0.03. This was consistent across procedure groups, with rotating staff acquiring higher ED compared to their scrub technician colleagues in diagnostic, interventional and electrophysiology cases. Statistically significant differences in radiation exposure of both staff groups were demonstrated in diagnostic and interventional cardiology procedures, with p-values of 0.04 and 0.01 respectively.(See Table) Conclusion: This small, single center study highlights occupational role as a significant factor in varying radiation exposure amongst non-physician staff . Higher ED was attributed to rotating staff duties involving proximity and mobility around fluoroscopy source and patient, devoid of protective lead shields. Based on these findings, avoiding fluoroscopy use while staff performs duties involving proximity to patient such is mandatory. Other essential measures should include accessory left sided leads shields, mandatory protective lens and head shields for rotating staff.